User satisfaction with Tokyo Metropolitan Government ward office counter services - Moteki, Yasutoshi (Frontiers in Built Environment, 2023)
This study clarifies the main factors affecting user satisfaction in public facilities using a two-part questionnaire, specifically, the determinants of service satisfaction among users of a ward office in Tokyo. The questionnaire comprised three main categories of multiple-choice questions: A) facility equipment (physical elements in the government office), B) staff responses, and C) service delivery (e.g., promptness of services, whether visitors completed their scheduled errands). In addition, the questionnaire investigated the users’ personalities of each facility. During a one-day survey, responses were collected from 400 women aged 30–59 years who had visited a ward office in the Tokyo Metropolitan Area within the previous month. This age segment was studied because it is the major segment of the panel of the internet research firm used. First, a factor analysis was used to check if the question groupings were appropriate based on eigenvalues and scree plots, and it was confirmed. Next, principal component and multiple regression analyses were conducted for each question category to examine the determinants of counter-service user satisfaction. The regression analysis, using the three main question categories and three other respondents’ personality-related question categories, shows that category C (service delivery quality) strongly influenced the dependent variable, followed by categories B and A. The adjusted R2 value was .70. This is consistent with the author’s surveys of government offices in urban areas conducted for Higashihiroshima City Hall and Osaka ward offices. Concerning the hardware aspect, the principal component loadings, the analysis results show that (1) indoor atmosphere, (2) ease of following the layout of the floors and offices inside the building, and (3) ease of understanding the building’s locations and entrances at the site of the ward office, are important factors for overall satisfaction at the ward office.